2005
DOI: 10.1021/jp053672q
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Interaction with Polycyclic Aromatic Hydrocarbons and Soot in Atmospheric Processes:  Theoretical Density Functional Study by Molecular and Periodic Methodologies

Abstract: The ozonization mechanism for polycyclic aromatic hydrocarbons (PAHs) and soot is investigated by quantum mechanical calculations carried out on molecular and periodic systems. PAHs, interesting per se, serve also to model the local features of the graphenic soot platelets, for which another model is provided by a periodic representation of one graphenic layer. A concerted addition leads to a primary ozonide, while a nonconcerted attack produces a trioxyl diradical (in which one of the two unpaired electrons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…7. This value appears to be unreasonably small since the the self-diffusion constant of squalane has been measured to be 3×10 35 . Currently, we cannot rule out this possibility and further study on reaction products in the thin shell layer may provide the necessary clue.…”
Section: B Ozone Transmission Through Reactive Shellmentioning
confidence: 96%
“…7. This value appears to be unreasonably small since the the self-diffusion constant of squalane has been measured to be 3×10 35 . Currently, we cannot rule out this possibility and further study on reaction products in the thin shell layer may provide the necessary clue.…”
Section: B Ozone Transmission Through Reactive Shellmentioning
confidence: 96%
“…A large number of experimental (Perraudin et al 2007;McCabe and Abbatt 2008;Bedjanian and Nguyen 2010;Shiraiwa et al 2011) and theoretical chemistry studies (Maranzana et al 2005;Giordana et al 2008) investigated the reactivity of ozone with soot particles and with PAHs deposited on different substrates. From these studies, the reactivity of O 3 with soot can be explained by a multi-step mechanism starting with (1) the physisorption of O 3 on the surface, which then undergoes dissociation to form a chemisorbed oxygen atom bound to the aromatic ring, and (2) the release of O 2 in the gas phase.…”
Section: Maturity Of Sootmentioning
confidence: 99%
“…Ketones and aldehydes have been identified as the main final products of the reaction leading to a local increase of the polarity of the surface, which enhances the uptake of water molecules. In particular, Maranzana et al, (Maranzana et al 2005;Giordana et al 2008) concluded from density function theory calculations that the energy barrier controlling the ozonization of internal positions is too high to be a viable option in atmospheric processes, and that it would be only possible for large graphene-like structures or very large concentration of O 3 and only after the reaction of the border positions. Therefore, the assumption that reactions with ozone takes place more favorably where the C-H bonds are abundant seems to be reasonable.…”
Section: Maturity Of Sootmentioning
confidence: 99%
“…The dissociated products are molecular oxygen such as a chemisorbed oxygen atom bound to the delocalized p-electrons of an aromatic surface. [49][50][51] The chemical equations of the multi-step L-H mechanism can be described as follows:…”
Section: Effect Of Humidity-induced Viscosity/diffusivity Changesmentioning
confidence: 99%